Resin cement paste as well as preparation method and application thereof

By using a special resin cement slurry in the shale gas well, combined with materials such as cement and epoxy resin, the problem of annular zone pressure after repeated fracturing of the shale gas well is solved, and the effect of efficient sealing and cost reduction is achieved.

CN119219364AActive Publication Date: 2024-12-31CHINA PETROLEUM & CHEMICAL CORP +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310776204.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2024-12-31
Estimated Expiration
2043-06-28

AI Technical Summary

Technical Problem

After repeated fracturing of shale gas wells, annular zone pressure problems are prone to occur, and the prior art is difficult to ensure the seal integrity and high cost of the solid sleeve in the sleeve.

Method used

A resin cement slurry is adopted, including cement, epoxy resin, curing agent, skeleton material, coagulation agent, toughening agent, dispersing agent, water reduction agent, defoaming agent and water, through specific ratios and stirring methods Prepare to form a composite system with excellent heat resistance, compressive strength and toughness, used for the sleeve and sleeve cementing of shale gas wells.

Benefits of technology

Effectively improve the impact resistance and sealing performance of resin cement slurry, reduce costs, meet the impact requirements of large-scale hydraulic fracturing after repeated fracturing of shale gas wells, extend the long-term seal of cement rings, and reduce the annular belt pressure. The occurrence of

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004309515900000121
    Figure BDA0004309515900000121
  • Figure BDA0004309515900000122
    Figure BDA0004309515900000122
  • Figure BDA0004309515900000131
    Figure BDA0004309515900000131
Patent Text Reader

Abstract

The invention relates to the field of drilling engineering, and discloses resin cement paste as well as a preparation method and application thereof. The resin cement paste comprises the following components in parts by weight: 100 parts of cement, 1-100 parts of epoxy resin, 1-80 parts of a curing agent, 1-100 parts of a framework material-I, 1-100 parts of a framework material-II, 0.1-40 parts of a thickening time control agent, 0.1-40 parts of a toughening agent, 1-40 parts of a dispersing agent, 0.1-20 parts of a fluid loss agent, 0.1-40 parts of a defoaming agent, 1-100 parts of water and 0-100 parts of a density regulator. The resin cement paste is prepared by selecting the components according to the specific parts by weight, the rheological property of the paste is good, well cementation construction is easy, and the obtained resin cement paste is higher in compressive strength and smaller in elastic modulus and can be used for a long time at the working temperature of 45-95 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of drilling engineering, and in particular to a resin cement slurry and a preparation method and application thereof. Background Art

[0002] The efficient development of shale gas reservoirs requires the use of large-scale hydraulic fracturing to form artificial fractures to provide seepage channels for production, but there are problems such as rapid production decline and short stable production period after the initial transformation. Repeated fracturing transformation technology is aimed at shale gas horizontal well clusters that are not fully transformed or insufficiently produced in the first time but still have potential for development. It is necessary to run a small casing in the original wellbore, cement the small casing, and then repeat fracturing to increase the production capacity of the shale gas well again. The technology of running a small casing in the old shale gas well for cementing is called casing-in-casing technology.

[0003] Compared with traditional oil and gas well cementing, the casing-in-casing technology has the following main technical difficulties: (1) The single-sided annular space of the casing-in-casing technology is small, and the annular pressure loss increases during the injection and replacement process, which brings great technical difficulties to leakage prevention and channeling prevention. (2) Later perforation and large-scale hydraulic fracturing have a great impact on the thin cement ring interface, and the sealing integrity of the thin cement ring is difficult to ensure, which easily forms annular pressure.

[0004] At present, in order to prevent annular pressure after repeated fracturing of shale gas wells, cement is mainly used to seal the annular space of the casing in the casing to prevent water loss. The disadvantage is that the traditional cement annulus is highly brittle and will break or even be crushed under pressure shock, resulting in annular pressure after repeated fracturing of shale gas wells. The disadvantage of simply using epoxy resin to seal the casing in the casing is that the cost is very high and the rheology is difficult to control.

[0005] Therefore, a fluid system with low elastic modulus and high toughness is needed to ensure the sealing integrity of the casing in the casing and reduce the problem of annular pressure after repeated fracturing of shale gas wells. Summary of the invention

[0006] The purpose of the present invention is to overcome the problems of increased annular pressure loss during injection and replacement in the existing casing-in-casing technology and the easy annular pressure after repeated fracturing of shale gas wells, and to provide a resin cement slurry and its preparation method and application.

[0007] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a resin cement slurry, wherein the resin cement slurry comprises the following components in parts by weight: 100 parts of cement, 1-100 parts of epoxy resin, 1-80 parts of curing agent, 1-100 parts of skeleton material-Ⅰ, 1-100 parts of skeleton material-Ⅱ, 0.1-40 parts of setting regulator, 0.1-40 parts of toughening agent, 1-40 parts of dispersant, 0.1-20 parts of fluid loss reducer, 0.1-40 parts of defoaming agent, 1-100 parts of water and 0-100 parts of density regulator.

[0008] A second aspect of the present invention provides a method for preparing the aforementioned resin cement slurry, characterized in that it comprises the following steps:

[0009] (1) Mix cement, epoxy resin, curing agent, skeleton material-II, setting regulator, toughening agent, dispersant, fluid loss reducer, defoaming agent, water and density regulator, and add them into a mixer;

[0010] (2) Stirring with a stirrer at a low speed, adding the skeleton material-Ⅰ powder within 5-15 seconds, and stirring with a stirrer at a high speed for 20-50 seconds, stirring evenly to obtain the resin cement slurry.

[0011] A third aspect of the present invention provides an application of the aforementioned resin cement slurry in casing cementing in repeated fracturing casing of a shale gas well.

[0012] Through the above technical solution, the beneficial technical effects achieved by the present invention are as follows:

[0013] (1) The resin cement slurry described in the present invention is a composite system of epoxy resin and cement, which has excellent heat resistance, good compressive strength and toughness, and excellent adhesion;

[0014] (2) The resin cement slurry of the present invention has good slurry rheology, is easy to cement, and has controllable curing time, which can meet the needs of cementing casing in repeated fracturing casing of shale gas wells at a temperature below 95°C;

[0015] (3) The present invention introduces epoxy resin materials and toughening agents into cement, which can effectively increase the elasticity of the solidified material while maintaining the original high strength of the cement, and has high impact resistance, which can meet the long-term sealing of the cement ring after the impact of large-scale hydraulic fracturing after perforating the thin cement ring;

[0016] (4) In the present invention, preferably, the use of a skeleton material can further improve or regulate the density, strength, rheology, curing time and other properties of the resin cement slurry system;

[0017] (5) In the present invention, the resin cement slurry has lower cost than the simple use of the resin system and has broad application prospects. DETAILED DESCRIPTION

[0018] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0019] The first aspect of the present invention provides a resin cement slurry, wherein the resin cement slurry comprises the following components in parts by weight: 100 parts of cement, 1-100 parts of epoxy resin, 1-80 parts of curing agent, 1-100 parts of skeleton material-Ⅰ, 1-100 parts of skeleton material-Ⅱ, 0.1-40 parts of setting regulator, 0.1-40 parts of toughening agent, 1-40 parts of dispersant, 0.1-20 parts of fluid loss reducer, 0.1-40 parts of defoaming agent, 1-100 parts of water and 0-100 parts of density regulator.

[0020] The present invention selects each component according to the above-mentioned specific weight parts to prepare resin cement slurry. The two skeleton materials and the added toughening agent and dispersant have a synergistic effect. The resin cement slurry prepared by combining with other components has good rheological properties and is easy for cementing construction. The obtained resin cement slurry has higher compressive strength, smaller elastic modulus, better hydrophilicity, and can be used for a long time at a working temperature of 45-95°C.

[0021] In the present invention, the casing-in-casing technology of shale gas wells requires higher strength and lower elastic modulus than traditional oil and gas well cementing due to the thinner cement ring and higher construction pump pressure. In order to meet the impact of large-scale hydraulic fracturing on the thin sealing ring, lower friction resistance is also required during construction to avoid high construction pump pressure, which will cause leakage of the formation and cause complex conditions underground.

[0022] According to the present invention, preferably, the weight parts of the components in the resin cement slurry based on the amount of cement are as follows: 100 parts of cement, 5-25 parts of epoxy resin, 5-50 parts of curing agent, 2-15 parts of skeleton material-Ⅰ, 5-50 parts of skeleton material-Ⅱ, 0.1-0.5 parts of setting agent, 1-10 parts of toughening agent, 1-5 parts of dispersant, 1-15 parts of fluid loss additive, 1-20 parts of defoaming agent, 20-80 parts of water and 0-80 parts of density regulator.

[0023] In the present invention, preferably, the cement is not particularly limited, and is preferably a Class G cement material in the field of cementing engineering.

[0024] In the present invention, the skeleton material can further improve or regulate the density, strength, rheology, curing time and other properties of the resin cement slurry system.

[0025] According to the present invention, preferably, the average particle size of the powder of the skeleton material-I is 10-1000 μm, preferably 10-500 μm. In the present invention, controlling the particle size of the skeleton material-I powder within the above preferred range allows it to fully react with the active ingredients in cement. The average particle size can be determined by sieving.

[0026] According to the present invention, preferably, the framework material-I is light-burned magnesium oxide.

[0027] In the present invention, preferably, the framework material-I can be prepared by the following method:

[0028] (1) dissolving magnesium nitrate and sodium bicarbonate in a certain amount of deionized water at a molar ratio of 1:1-3, then adjusting the pH value of the solution to 3-4 with dilute nitric acid to obtain solution A, heating solution A in a water bath to 50-70° C., dissolving anhydrous Na2CO3 in deionized water to obtain solution B with a concentration of 1-2 mol / L, adjusting the pH value to 9-10 with concentrated nitric acid, and then heating solution B in a water bath at 50-70° C.;

[0029] (2) While stirring at a speed of 500-1500 r / min, solution B is quickly added to solution A and the stirring is continued for 2-10 min, and the solution is allowed to stand for aging for 10-60 min. The product is then filtered, washed with ultrapure water and ethanol, and dried at 80-120° C. to obtain MgCO3.

[0030] (3) Calcine MgCO3 at 300-900°C for 10-24h to obtain MgO, and then ball mill it for 20-60min to obtain MgO particles.

[0031] According to the present invention, preferably, the weight of the skeleton material-Ⅰ is 1-100 parts, which can be 1 part, 5 parts, 10 parts, 20 parts, 30 parts, 40 parts, 50 parts, 60 parts, 70 parts, 80 parts, 90 parts, 100 parts, and any value in the range of any two of the above values, preferably 2-15 parts. Adding the above preferred weight parts of skeleton material-Ⅰ can improve the thickening performance and compressive strength of cement slurry, but too much addition of skeleton material-Ⅰ will make the elastic modulus of resin cement slurry too large, which cannot meet the needs of large-scale fracturing in the later stage of shale gas wells.

[0032] According to the present invention, preferably, the framework material-II is selected from at least one of magnesium chloride, magnesium phosphate and magnesium sulfate.

[0033] In the present invention, preferably, the weight proportion of the skeleton material-II is 1-100 parts, and can be 1 part, 5 parts, 10 parts, 20 parts, 30 parts, 40 parts, 50 parts, 60 parts, 70 parts, 80 parts, 90 parts, 100 parts, and any value in the range composed of any two of the above values, preferably 5-50 parts.

[0034] According to the present invention, preferably, the epoxy resin is selected from at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin and hydrogenated bisphenol A epoxy resin, preferably selected from at least one of bisphenol F epoxy resin, bisphenol S epoxy resin and hydrogenated bisphenol A epoxy resin.

[0035] In the present invention, preferably, the weight portion of the epoxy resin is 1-100 parts, and can be 1 part, 5 parts, 10 parts, 20 parts, 25 parts, 30 parts, 40 parts, 50 parts, 60 parts, 70 parts, 80 parts, 90 parts, 100 parts, and any value in the range consisting of any two of the above values, preferably 5-25 parts.

[0036] According to the present invention, preferably, the viscosity of the epoxy resin is 10-1000 mPa·s, preferably 100-800 mPa·s.

[0037] According to the present invention, preferably, the epoxy equivalent of the epoxy resin is 10-2000 g / mol, preferably 100-1000 g / mol.

[0038] In the present invention, preferably, by adding epoxy resin to the resin cement slurry, the elasticity of the cured product can be effectively increased while maintaining a relatively high strength, and the product has a relatively high impact resistance, which can meet the requirements of long-term sealing of the cement ring after the impact of large-scale hydraulic fracturing after perforating the thin cement ring.

[0039] According to the present invention, preferably, the curing agent is selected from at least one of monofunctional anhydrides, difunctional anhydrides, free acid anhydrides, maleic anhydride, phenolic resin, polyester resin, styrene-maleic anhydride copolymer resin and polysulfide rubber.

[0040] Preferably, the curing agent is selected from at least one of monofunctional anhydrides, difunctional anhydrides, free acid anhydrides, styrene-maleic anhydride copolymer resin and polysulfide rubber. More preferably, the curing agent is selected from at least one of phthalic anhydride, succinic anhydride and maleic anhydride.

[0041] According to the present invention, preferably, the weight proportion of the curing agent is 1-80 parts, and can be 1 part, 5 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, and any value in the range consisting of any two of the above values, preferably 5-50 parts.

[0042] In the present invention, preferably, the epoxy resin is an epoxy resin emulsion, which forms a thermosetting resin gelling system with a curing agent.

[0043] In the present invention, the thermosetting resin gelling material in the thermosetting resin gelling system can be cross-linked and cured under heating and pressurizing conditions to form a mesh structure, which is not easily deformed under pressure and has the advantages of good adhesion, impact resistance, low elastic modulus, high toughness, etc. The use of the skeleton material of the present invention can further improve or regulate the density, strength, rheology, and curing time of the thermosetting resin system, and while meeting the basic requirements of cementing engineering, it can also solve the problems of difficulty in ensuring the sealing integrity of thin cement rings and poor bonding.

[0044] According to the present invention, preferably, the toughening agent is an elastic material, preferably a plasma-modified elastic material. In the present invention, the elastic material is subjected to plasma modification to change its surface activity. The surface polar groups of unmodified rubber particles are relatively few and the hydrophilicity is poor. Polar groups are generated on the surface of the plasma-modified elastic material, the hydrophilicity is significantly improved, the surface tension is smaller, and the toughness of the resin cement slurry can be improved.

[0045] In the present invention, preferably, the elastic material is rubber particles.

[0046] In the present invention, the plasma modification adopts a plasma treatment apparatus, which mainly includes a discharge system, a reaction chamber, an air intake system, an electromagnetic shield, a vacuum system and a gas discharge system, with a discharge frequency of 13.56 MHz and a maximum power of 400 W.

[0047] In the present invention, preferably, the modification process comprises: subjecting the elastic material to plasma treatment under an inert atmosphere, wherein the plasma is argon gas with a purity of 98%-99.999%, the plasma flow rate is 1-100 sccm, the discharge power is 10-400 W, and the treatment time is 2-10 min.

[0048] In the present invention, preferably, the inert atmosphere is argon with a purity of >99.999%.

[0049] According to a preferred embodiment of the present invention, the modification power of the plasma modification is 80w, the modification time is 180s, the low-temperature plasma instrument is preheated for 30min, the vacuum pump is turned on, and when the vacuum degree in the chamber is reduced to below 10Pa, the purity of the modified gas is ensured, the flow valve is opened, and the modified gas is put in with a flow rate stabilized at 60sccm, the modification time is set to 180s, and it is stopped after reaching the set parameters. Then the modified elastic material is put into a planetary ball mill for ball milling for 1h to obtain a plasma-modified elastic material.

[0050] In the present invention, the surface activity of the elastic material before and after modification is determined, and the contact angle between the sample surface and a droplet (deionized water) in an atmospheric environment is measured using a contact angle device CA500S integral tilt fully automatic optical contact angle measuring instrument. The standard ASTM 5725 / standard method for testing the surface wettability and absorbency of sheet materials using an automatic contact angle tester is implemented to characterize the surface wettability and aging properties of the elastic material before and after modification.

[0051] According to the present invention, preferably, the weight portion of the toughening agent is 0.1-40 parts, and can be 0.1 parts, 1 parts, 5 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, and any value in the range composed of any two of the above values, preferably 1-10 parts.

[0052] According to the present invention, preferably, the dispersant is selected from polycarboxylic acid dispersants and / or aldehyde ketone dispersants, preferably polycarboxylic acid dispersants.

[0053] In the present invention, the dispersant can effectively disperse the solid phase particles at room temperature and high temperature to improve the rheological properties of the slurry.

[0054] In the present invention, preferably, the weight portion of the dispersant is 0.1-40 parts, and can be 0.1 parts, 1 parts, 5 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, and any value in the range consisting of any two of the above values, preferably 1-5 parts.

[0055] According to the present invention, preferably, the setting agent is selected from at least one of polyphosphate setting agents, citrate setting agents and gluconate setting agents, preferably a polyphosphate setting agent.

[0056] In the present invention, the setting regulator can control the thickening time of the resin cement slurry within the temperature range of 45-95°C.

[0057] According to the present invention, preferably, the weight portion of the setting agent is 0.1-40 parts, and can be 0.1 parts, 0.5 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, and any value in the range composed of any two of the above values, preferably 0.1-0.5 parts.

[0058] According to the present invention, preferably, the defoamer is selected from at least one of silicone oil defoamers, polyether defoamers and aldehyde ketone defoamers. In the present invention, the use of the above defoamers can effectively control the generation of foam in the cement slurry system and improve the compressive strength of the resin cement slurry.

[0059] According to the present invention, preferably, the weight portion of the defoaming agent is 0.1-40 parts, and can be 0.1 parts, 0.5 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, and any value in the range composed of any two of the above values, preferably 1-20 parts.

[0060] According to the present invention, preferably, the fluid loss agent is selected from polyvinyl alcohol fluid loss agent and / or 2-acrylamide-2-methylpropanesulfonic acid fluid loss agent, preferably a polyvinyl alcohol fluid loss agent, more preferably polyvinyl pyrrolidone and / or polyvinyl alcohol.

[0061] In the present invention, the fluid loss reducer can control the filtration rate of cement slurry in the resin cement slurry system, thereby preventing annular air breakthrough.

[0062] According to the present invention, preferably, the weight portion of the fluid loss agent is 0.1-20 parts, and can be 0.1 parts, 0.5 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 8 parts, 10 parts, 12 parts, 14 parts, 15 parts, 20 parts, and any value in the range consisting of any two of the above values, preferably 1-15 parts.

[0063] According to the present invention, the density regulator is a lightening agent or a weighting agent, and the density regulator is used to adjust the density of the resin cement slurry to 1.2-1.7 g / cm 3 within the range.

[0064] According to the present invention, preferably, the lightening agent is floating beads, preferably high anti-extrusion glass beads.

[0065] According to the present invention, preferably, the weighting agent is selected from at least one of hematite powder, iron ore powder and magnetite powder.

[0066] According to the present invention, preferably, the weight proportion of the density regulator is 0-100 parts, and may be 0 parts, 10 parts, 20 parts, 30 parts, 40 parts, 50 parts, 60 parts, 70 parts, 80 parts, 90 parts, 100 parts, and any value in the range consisting of any two of the above values, preferably 0-80 parts.

[0067] According to the present invention, preferably, the water is not particularly limited, as long as the resin cement slurry can be prepared. The weight of the water is 1-100 parts, and can be 1 part, 5 parts, 10 parts, 20 parts, 30 parts, 40 parts, 50 parts, 60 parts, 70 parts, 80 parts, 90 parts, 100 parts, and any value in the range of any two of the above values, preferably 20-80 parts.

[0068] A second aspect of the present invention provides a method for preparing the aforementioned resin cement slurry, comprising the following steps:

[0069] (1) Mix cement, epoxy resin, curing agent, skeleton material-II, toughening agent, setting regulator, dispersant, fluid loss reducer, defoamer, water and density regulator, and add them into a mixer;

[0070] (2) Stirring with a stirrer at a low speed, adding the skeleton material-Ⅰ powder within 5-15 seconds, and stirring with a stirrer at a high speed for 20-50 seconds, stirring evenly to obtain the resin cement slurry.

[0071] In the present invention, the stirring speed of the stirrer for low-speed stirring is 3500-4500 rpm, and the stirring speed of the stirrer for high-speed stirring is 10000-14000 rpm.

[0072] Furthermore, the stirring speed of the stirrer for low-speed stirring is 3800-4200 rpm, and the stirring speed for high-speed stirring is 11000-13000 rpm. Under the above stirring conditions, each component and the skeleton material-Ⅰ powder can be quickly mixed uniformly to obtain a resin cement slurry with good rheology and good impact resistance.

[0073] A third aspect of the present invention provides an application of the aforementioned resin cement slurry in casing cementing in repeated fracturing casing of a shale gas well.

[0074] In the present invention, the resin cement slurry can be used at 45-95° C., has a wide temperature application range and good sealing effect.

[0075] According to a particularly preferred embodiment of the present invention, the resin cement slurry comprises the following components in parts by weight: 100 parts of cement, 5-20 parts of epoxy resin, 5-50 parts of curing agent, 2-10 parts of skeleton material-Ⅰ, 5-50 parts of skeleton material-Ⅱ, 0.1-0.4 parts of setting agent, 1-10 parts of toughening agent, 1-5 parts of dispersant, 1-15 parts of fluid loss additive, 1-20 parts of defoaming agent, 20-80 parts of water and 0-80 parts of density regulator.

[0076] In the following examples and comparative examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if no manufacturer is specified, are conventional products that can be obtained through commercial channels;

[0077] The epoxy equivalent of the bisphenol F epoxy resin and the bisphenol S epoxy resin in the examples and comparative examples is 170 g / mol and the viscosity is 200 mPa·s;

[0078] The polyvinyl alcohol was polyvinyl alcohol 1788 purchased from Aladdin.

[0079] The density, thickening performance, API water loss, stability, compressive strength and rheological parameters of resin cement slurry are measured in accordance with GB / T 19139-2012 Test Methods for Oil Well Cement;

[0080] The elastic modulus of the resin cement slurry is measured by a mechanical properties testing machine according to "Mechanical properties of high temperature and high pressure resistant ultra-high density cement stone" (Song He, Yang Wei, Tang Junfeng, et al. "Drilling Fluid and Completion Fluid" [J], 2021(038-006)).

[0081] Framework Material-Ⅰ Preparation Example

[0082] Dissolve 1 mol of magnesium nitrate and 1 mol of sodium bicarbonate in 500 mL of deionized water, then adjust the solution pH to 4 with dilute nitric acid to obtain solution A, and place solution A in a water bath and heat it to 65°C; dissolve 1 mol of anhydrous Na2CO3 in 500 mL of deionized water to prepare solution B, adjust the pH to 10, and then place solution B in a 65°C water bath and heat it. Under stirring at 1000 r / min, quickly add solution B to solution A and continue stirring for 4 minutes, and then let it stand and age for 30 minutes.

[0083] The product was then filtered, washed with ultrapure water and ethanol for 5 times, and dried at 100°C for 12 hours to obtain MgCO3. MgCO3 was calcined at 600°C for 12 hours in a muffle furnace to obtain MgO, which was then placed in a planetary ball mill for 30 minutes and then taken out to obtain MgO with a particle size of 10-500 μm.

[0084] Test Example 1

[0085] The surface activity of the elastic material before and after modification was determined, and the elastic material samples were subjected to tabletting treatment.

[0086] The contact angle between the sample surface and the droplet (deionized water) in the atmospheric environment was measured using a contact angle device CA500S integral tilt fully automatic optical contact angle meter. The standard ASTM 5725 was implemented, and the standard method for testing the surface wettability and absorbency of sheet materials using an automatic contact angle tester was used to characterize the surface wettability and aging of the elastic material before and after modification. The contact angle was measured three times, and the results are shown in Table 1.

[0087] Table 1

[0088] Elastic material before modification Modified elastic material Contact angle (°) 136 / 128 / 127 38 / 39 / 37

[0089] It can be seen from Table 1 that the water contact angles on the surface of the elastic material before plasma modification are 136 / 128 / 127°, showing hydrophobic properties. From the contact angles of the elastic material after plasma modification, it can be seen that plasma has significantly improved the wetting properties of the elastic material surface, and the water contact angles have all dropped to below 40°, greatly improving the hydrophilicity of the elastic material.

[0090] Example 1

[0091] (1) 100 parts of G-grade cement in the cementing engineering field, 20 parts of epoxy resin, 20 parts of curing agent, 5 parts of magnesium chloride, 0.2 parts of setting agent, 4 parts of toughening agent, 3 parts of dispersant, 3 parts of fluid loss additive, 2 parts of defoaming agent, 50 parts of water and 50 parts of density regulator were mixed and added into a mixer. The specific types of substances are shown in Table 2;

[0092] (2) The stirrer is stirred at a low speed of 4000 rpm, and the skeleton material-Ⅰ powder is added within 15 seconds. The stirrer lid is closed and the stirrer is stirred at a high speed for 35 seconds. The resin cement slurry is obtained by stirring evenly.

[0093] Example 2-20

[0094] Resin cement slurry was prepared according to the formula (parts by weight) in Table 2 with reference to the preparation method of Example 1.

[0095] Table 2 Table 2 (continued)

[0096]

[0097]

[0098] Table 2 (continued)

[0099]

[0100] Table 2 (continued)

[0101]

[0102]

[0103] Table 2 (continued)

[0104]

[0105]

[0106] Comparative Examples 1-5

[0107] Resin cement slurry was prepared according to the formula (parts by weight) in Table 3 and the preparation method of Example 1.

[0108] Table 3

[0109]

[0110]

[0111] Test Case

[0112] The density, API water loss, thickening performance and compressive strength of the resin cement slurries of Examples 1-8 and Comparative Example 1 were measured according to the aforementioned method. The specific results are shown in Table 4.

[0113] Table 4

[0114]

[0115] It can be seen from Table 4 that the resin cement slurry of the embodiment of the present invention has strong stability. The preferred epoxy resin type and curing agent type have an effect on the thickening time, but they are within the adjustable range. The API water loss is less than 50mL / 30min. In the comparative example, since the amount of epoxy resin added exceeds the recommended range, the thickening time cannot meet the construction needs. Example 7 Changing the type of setting agent has little effect on the entire cement slurry system. Example 8 Changing the type of skeleton material II has a slight effect on the thickening time, but it is still acceptable.

[0116] The density, compressive strength and elastic modulus of the resin cement slurry of Examples 9-10, 15-16 and Comparative Example 4 were measured according to the aforementioned test methods. The specific results are shown in Table 5.

[0117] Table 5

[0118] serial number <![CDATA[Density, g / cm 3 > Compressive strength, 95℃ / 48h, MPa Elastic modulus, GPa Example 1 1.65 25.3 4.8 Example 9 1.60 22.1 4.5 Example 10 1.55 20.2 4.0 Embodiment 15 1.66 22.2 4.4 Example 16 1.67 20.6 4.1 Comparative Example 4 1.65 28.8 6.9

[0119] It can be seen from Table 5 that the compressive strength of the resin cement slurry prepared in Example 1 is higher. As the density decreases, the compressive strength of the cement stone gradually decreases, and the elastic modulus also changes accordingly, allowing the cement ring to maintain a low elastic modulus while meeting the high strength requirement. The elastic modulus is kept below 5 GPa, ensuring the toughness of the resin cement slurry, so that it can meet the needs of large-scale fracturing in the later stage of shale gas wells. In Examples 15 and 16, the elastic modulus decreases and the compressive strength increases due to the increase in the amount of toughening agent. In Comparative Example 4, since no toughening agent is added, the compressive strength and elastic modulus are higher than those of the embodiment, but for the sleeve-in-sleeve process, the narrow gap thin cement ring requires a higher compressive strength and a lower elastic modulus to meet the development requirements.

[0120] The density, API water loss and thickening performance of the resin cement slurries of Examples 11-12 and Comparative Examples 1-2 were measured according to the aforementioned method. The specific results are shown in Table 6.

[0121] Table 6

[0122]

[0123] It can be seen from Table 6 that the thickening time of the resin cement slurry in Example 1 of the present invention is adjustable under the action of the setting regulator and does not affect the water loss of API. In contrast, since the addition amount of Comparative Examples 1 and 2 exceeds the recommended range, the thickening time cannot meet the on-site process requirements.

[0124] The density and thickening performance of the resin cement slurry of Examples 13-14 were measured according to the aforementioned method. The specific results are shown in Table 7.

[0125] Table 7

[0126] serial number <![CDATA[Density, g / cm 3 > Thickening performance 95℃ / 45MPa, min Example 1 1.65 431 Example 13 1.62 587 Embodiment 14 1.60 634 Comparative Example 1 1.45 82

[0127] It can be seen from Table 7 that the resin cement slurries in Examples 13 and 14 of the present invention have a slightly longer thickening time due to the larger amount of epoxy resin added, but are still within the adjustable range.

[0128] The rheological parameters and elastic modulus of the resin cement slurries of Examples 15-18 and Comparative Examples 3-4 at room temperature and high temperature were measured according to the aforementioned method. The specific results are shown in Table 8.

[0129] Table 8

[0130]

[0131] It can be seen from Table 8 that compared with the resin cement slurry of Example 1, Examples 15 and 16 of the present invention have higher rheological parameters due to the larger amount of toughening agent added. The rheological parameters tested at the same rotation speed are much higher than those of Example 1. The slurry is basically unable to flow. Although the elastic modulus can be reduced, it cannot meet the rheological requirements of on-site construction. The resin cement slurries of Examples 17 and 18 have better rheological properties and are in a thinner state due to the increased amount of dispersant added. In Comparative Example 3, since no dispersant was added, the rheological properties are poor. In Comparative Example 4, since no toughening agent was added, the rheological properties are better, but due to the high elastic modulus, it cannot meet the requirements of cement slurry for solid casing in shale gas well casings.

[0132] The density, thickening performance and compressive strength of the resin cement slurry of Examples 19-20 and Comparative Example 5 were measured according to the aforementioned method. The specific results are shown in Table 9.

[0133] Table 9

[0134]

[0135] It can be seen from Table 9 that the thickening performance and compressive strength of the resin cement slurry in Examples 19 and 20 are affected by the change in the amount of skeleton material-I. As the amount of skeleton material-I increases, the thickening time of the cement slurry decreases and the compressive strength of the cement paste increases. Comparative Example 5 has a longer thickening time and lower compressive strength due to the lack of skeleton material.

[0136] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A resin cement slurry, characterized in that: The resin cement slurry comprises the following components in parts by weight: 100 parts of cement, 1-100 parts of epoxy resin, 1-80 parts of curing agent, 1-100 parts of skeleton material-Ⅰ, 1-100 parts of skeleton material-Ⅱ, 0.1-40 parts of setting regulator, 0.1-40 parts of toughening agent, 1-40 parts of dispersant, 0.1-20 parts of fluid loss reducer, 0.1-40 parts of defoaming agent, 1-100 parts of water and 0-100 parts of density regulator.

2. The resin cement slurry according to claim 1, wherein: The weight proportions of the components in the resin cement slurry based on the amount of cement are as follows: 100 parts of cement, 5-25 parts of epoxy resin, 5-50 parts of curing agent, 2-15 parts of skeleton material-Ⅰ, 5-50 parts of skeleton material-Ⅱ, 0.1-0.5 parts of setting agent, 1-10 parts of toughening agent, 1-5 parts of dispersant, 1-15 parts of fluid loss reducer, 1-20 parts of defoaming agent, 20-80 parts of water and 0-80 parts of density regulator.

3. The resin cement slurry according to claim 1 or 2, wherein: The average particle size of the powder of the framework material-Ⅰ is 10-1000 μm, preferably 10-500 μm; Preferably, the framework material-I is light-burned magnesium oxide; Preferably, the framework material-II is selected from at least one of magnesium chloride, magnesium phosphate and magnesium sulfate.

4. The resin cement slurry according to any one of claims 1 to 3, wherein: The epoxy resin is selected from at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin and hydrogenated bisphenol A epoxy resin, preferably selected from at least one of bisphenol F epoxy resin, bisphenol S epoxy resin and hydrogenated bisphenol A epoxy resin; Preferably, the viscosity of the epoxy resin is 10-1000 mPa·s, preferably 100-800 mPa·s; Preferably, the epoxy equivalent of the epoxy resin is 10-2000 g / mol, preferably 100-1000 g / mol.

5. The resin cement slurry according to any one of claims 1 to 4, wherein: The curing agent is selected from at least one of monofunctional acid anhydride, difunctional acid anhydride, free acid anhydride, maleic anhydride, linear phenolic resin, polyester resin, styrene-maleic anhydride copolymer resin and polysulfide rubber, preferably selected from at least one of monofunctional acid anhydride, difunctional acid anhydride, free acid anhydride, styrene-maleic anhydride copolymer resin and polysulfide rubber.

6. The resin cement slurry according to any one of claims 1 to 5, wherein: The dispersant is a polycarboxylic acid dispersant and / or an aldehyde ketone dispersant, preferably a polycarboxylic acid dispersant; Preferably, the toughening agent is an elastic material, preferably a plasma-modified elastic material; Preferably, the contact angle of the plasma-modified elastic material is less than 50°, preferably 20°-40°.

7. The resin cement slurry according to any one of claims 1 to 6, wherein: The coagulant is selected from at least one of a polyphosphate coagulant, a citrate coagulant and a gluconate coagulant, preferably a polyphosphate coagulant; Preferably, the defoamer is selected from at least one of silicone oil defoamers, polyether defoamers and aldehyde-ketone defoamers; Preferably, the fluid loss agent is a polyvinyl alcohol fluid loss agent and / or 2-acrylamide-2-methylpropane sulfonic acid, preferably a polyvinyl alcohol fluid loss agent.

8. The resin cement slurry according to any one of claims 1 to 7, wherein: The density modifier is a lightening agent or a weighting agent; Preferably, the lightening agent is floating beads; Preferably, the weighting agent is selected from at least one of hematite powder, iron ore powder and magnetite powder.

9. A method for preparing the resin cement slurry according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) Mix cement, epoxy resin, curing agent, skeleton material-II, setting regulator, toughening agent, dispersant, fluid loss reducer, defoaming agent, water and density regulator, and add them into a mixer; (2) Stirring with a stirrer at a low speed, adding the skeleton material-Ⅰ powder within 5-15 seconds, and stirring with a stirrer at a high speed for 20-50 seconds, stirring evenly to obtain the resin cement slurry.

10. Use of the resin cement slurry according to any one of claims 1 to 8 in casing cementing in shale gas well re-fracturing casing.

Citation Information

Patent Citations

  • Low temperature magnesium oxysulfide thermosetting resin cementitious system and preparation method thereof

    CN109536144A

  • Elastic modified resin for oil well cement and preparation method and application thereof

    CN110845705A

  • Elastic and tough resin cement slurry for well cementing and preparation method of elastic and tough resin cement slurry

    CN110862246A